A computational and conceptual DFT study on the mechanism of hydrogen activation by novel frustrated Lewis pairs1. Issue 16 (28th April 2015) - Pérez, Patricia; Yepes, Diana; Jaque, Pablo; Chamorro, Eduardo; Domingo, Luis R.; Rojas, Rene S.; Toro-Labbé, Alejandro
<x xml:space="preserve">Abstract</x> The activation of molecular hydrogen, H2, by three models of FLPs.